2015
DOI: 10.1103/physrevlett.114.110602
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuniformity of Critical Absorbing States

Abstract: The properties of the absorbing states of non-equilibrium models belonging to the conserved directed percolation universality class are studied. We find that at the critical point the absorbing states are hyperuniform, exhibiting anomolously small density fluctuations. The exponent characterizing the fluctuations is measured numerically, a scaling relation to other known exponents is suggested, and a new correlation length relating to this ordering is proposed. These results may have relevance to photonic band… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
240
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(266 citation statements)
references
References 14 publications
23
240
3
Order By: Relevance
“…2 for a vivid illustration. During the last decade, a variety of disordered hyperuniform states have been identified that exist as both equilibrium and nonequilibrium phases, including maximally random jammed particle packings [33][34][35][36], jammed athermal granular media [37], jammed thermal colloidal packings [38,39], cold atoms [40], transitions in nonequilibrium systems [41,42], surfaceenhanced Raman spectroscopy [43], terahertz quantum cascade laser [44], wave dynamics in disordered potentials based on supersymmetry [45], avian photoreceptor patterns [46], and certain Coulombic systems [47]. Moreover, disordered hyperuniform materials possess novel physical properties potentially important for applications in photonics [25][26][27]48,49] and electronics [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…2 for a vivid illustration. During the last decade, a variety of disordered hyperuniform states have been identified that exist as both equilibrium and nonequilibrium phases, including maximally random jammed particle packings [33][34][35][36], jammed athermal granular media [37], jammed thermal colloidal packings [38,39], cold atoms [40], transitions in nonequilibrium systems [41,42], surfaceenhanced Raman spectroscopy [43], terahertz quantum cascade laser [44], wave dynamics in disordered potentials based on supersymmetry [45], avian photoreceptor patterns [46], and certain Coulombic systems [47]. Moreover, disordered hyperuniform materials possess novel physical properties potentially important for applications in photonics [25][26][27]48,49] and electronics [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…In dense regions (typically defined as more than 2 particles in a given neighborhood), particles are active and follow a prescribed dynamics (typically perform jumps); otherwise particles are said to be passive and remain at rest. Several microscopic models in this class have been proposed, including the Manna model, the random organization (RandOrg) model or the conserved lattice gas model and their generalizations; these are either on or off lattice, and involve different choices of kinetic rules [5,7,10,[14][15][16][17]. Recently, a renewed interest in this class of models was triggered by [15,16], where it was found that the fluctuations in density in models belonging to the Manna class scale differently than usual random systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [15], a variety of models belonging to the Manna class were shown to display hyperuniformity (γ>d) at the critical point. This is in contrast with classical equilibrium models in which fluctuations are enhanced at the critical point (γ<d) [18].…”
Section: Introductionmentioning
confidence: 99%
“…We start with a one dimensional rectangular particle of length p, that covers p/p o pixels and has volume V P = I o p. The sums in Eqs. (16)(17)(18)(19) with I(i) = I o are readily evaluated. Dividing V R V Q 2 by V P V Ω 2 = I o pL 2 then gives the predicted relative variance for random particle placements as…”
Section: Rectangular Particlesmentioning
confidence: 99%
“…Examples include jamming in amorphous materials [4,5,[7][8][9][10], complete optical band gaps in disordered photonics materials [11][12][13][14][15], and reversibility/irreversibility in periodically driven systems [16][17][18]. Hyperunformity is also important in the arrangement of photoreceptors in the retina [19], and in the large-scale structure of the universe [2].…”
mentioning
confidence: 99%